(untitled) (Altre Modernità, 2019)
This essay offers an interpretation of John Maxwell Coetzee’s Diary of a Bad Year and its main character JC in relation to the South Africa’s colonial past. I critically discuss the traditional point of view on Coetzee’s Boyhood, Youth and Summertime as parts of an ‘autobiographical trilogy’ (Attwell). In this analysis I propose to read the mentioned novels and Diary of a Bad Year as parts of an ‘autofictional tetralogy’. This proposal is based on two elements: on one hand, on characters’ strong grade of independence from their author – as Coetzee himself has pointed out (Auster-Coetzee) – and on coherence in psychological and intellectual development of the four mentioned novels’ main characters; on the other hand, since I see these characters as different expressions of the same individual, on their sharing the same cultural background. The focus is on JC because the relation with SA’s colonial past is evident in him: his choice to use essayistic writing, his effort in writing in general – in spite of his lack of endurance – and his use of ‘diary’ specific elements can be seen as residuals of the colonial ‘fight to idleness’ taught SA natives by English and Dutch protestant colonizers. Using JC as a model, this essay explains how the practical applications of that colonial concept have changed going through the times under different forms.